Evaluación del Crecimiento Vegetativo de la Jícama (smallanthus sonchifolius), mediante dos Técnicas de Propagación (estacas e hijuelos) con la adición de dos Abonos Orgánicos (Compost de Vaca y Cuy), en el Cantón Salcedo, periodo 2018-2019. - Suatunce Dias, Ana Lucia (2019)
The purpose of the present work was to evaluate the vegetative growth of the jicama (Smallanthus sonchifolius), by means of two propagation techniques (stakes and regrowth) with the addition of two organic fertilizers (cow compost and guinea pig), in the Canton Salcedo at an altitude of 2734 msnm, with properties of sandy loam soil with a pH of 7.23. We worked with a Design of Random Complete Blocks (DBCA), where 2 propagation techniques (cuttings and stakes), two organic fertilizers (cow compost, guinea pig compost and the control) were evaluated, with 4 repetitions. With a total of 24 experimental units. For the variables, the variance analysis and the Tukey significance test were performed at 5% in the treatments. In order to achieve the proposed objectives, the following variables were analyzed: Plant height, base diameter, number of leaves, leaf length and diameter, number of shoots, number of branches, adaptation of cuttings and emergence of regrowth and percentage of affectation by frost The results obtained in the different variables were in height of the plant, it was observed that the treatment T4 (regrowth + guinea pig compost), obtained an average of 61.42 cm, being the highest value compared to the other treatments, the base diameter It was of 15.91 mm, in the number of leaves thrown an average of 328.17 per plant, in length and diameter of leaf was obtained an average of 30.99 cm long and 118.71cm wide respectively, the number of shoots average of 5.06 plant, in as for the branches of 39.03 branches per plant. In the percentage of emergence for regrowth of 100% and adaptation of stake 66.11%. The average percentage of affectation by frost for the cuttings was of 44.5% and for the shoots of 35.58%, demonstrating that the suckers tolerate an 8.92% of resistance to the frosts compared to the stakes. Regarding the organic sources, the compost of guinea pig compost reflex better results in height obtained an average of 5.15 cm, a base diameter of 6.11 mm, leaf length of 6.83 cm and diameter of 3.67 cm. In view of the results, it can be concluded that T4 (regrowth + guinea pig compost) generated higher results based on the variables under study, which can generate benefits for the farmer, promoting interest in the crop.